METHODOLOGICAL FOUNDATIONS OF CREATIVE COMPETENCE DEVELOPMENT IN STUDENTS BASED ON AN INNOVATIVE APPROACH (Multidisciplinary Journal of Science and Technology, 2024)
This article delves into the methodological foundations essential for developing creative competence in students, emphasizing the need for innovative approaches to teaching and learning. It identifies key components of creative competence, such as imagination, problem-solving, critical thinking, collaboration, and communication. The article explores various innovative teaching methods, including project-based learning, inquiry-based learning, flipped classrooms, gamification, and technology integration. It also discusses strategies for implementing these approaches, such as teacher training, curriculum design, and creating supportive learning environments. Additionally, the article highlights case studies and addresses challenges in adopting innovative methods, providing practical solutions to overcome these obstacles. Overall, it underscores the importance of fostering creative competence to prepare students for future challenges